2022
DOI: 10.21037/atm-22-2721
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden and long-term mortality in survivors of extracorporeal membrane oxygenation in South Korea

Abstract: Background: The economic burden for extracorporeal membrane oxygenation (ECMO) survivors is a critical issue. We investigated the total healthcare costs for one year following ECMO support and its association with three-year all-cause mortality.Methods: This population-based cohort study used data from the National Health Insurance Service (NHIS) in South Korea. Adult ECMO survivors (age ≥18 years who were alive ≥365 days following ECMO support) from January 1, 2005, to December 31, 2018, were included. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Of 28 SES studies, 14 studies (50%) were conducted outside the United States. Nine examined Income in the South Korean National Health Insurance (NHI), with four finding no association with ECMO complications or mortality (108)(109)(110)(111) and five reporting statistical associations without a consistent dose-dependent income response (112)(113)(114)(115)(116). One Chinese National Clinical Improvement System population-level study found that areas with mid-level Gross Domestic Product (vs high) had a lower mortality (117) and single-center study showed employment was associated with quality of life in survivors (118).…”
Section: Ecmo Outcomesmentioning
confidence: 99%
“…Of 28 SES studies, 14 studies (50%) were conducted outside the United States. Nine examined Income in the South Korean National Health Insurance (NHI), with four finding no association with ECMO complications or mortality (108)(109)(110)(111) and five reporting statistical associations without a consistent dose-dependent income response (112)(113)(114)(115)(116). One Chinese National Clinical Improvement System population-level study found that areas with mid-level Gross Domestic Product (vs high) had a lower mortality (117) and single-center study showed employment was associated with quality of life in survivors (118).…”
Section: Ecmo Outcomesmentioning
confidence: 99%
“…In this issue of the Annals of Translational Medicine, Oh et al ( 4 ) shared the results from a population-based, nationwide, retrospective cohort study. This study comprised a total of 6,044 patients, with a range of indications requiring ECMO support, such as cardiac (59.0%), respiratory (10.9%) and other causes (30.1%).…”
mentioning
confidence: 99%
“…Initial entry into type 2 pneumocytes in the lungs via ACE2 receptors has been shown to trigger an inflammatory cytokine response, which can subsequently lead to acute respiratory distress syndrome (ARDS) ( 3 ). This is where extracorporeal membrane oxygenation (ECMO) comes into play; displaying its benefits as a rescue therapy in the intensive care unit when mechanical ventilation has failed in this regard ( 4 ). The utilisation of ECMO was soon encouraged by the WHO and Extracorporeal Life Support Organisation (ELSO) and advocated through interim guidelines as part of the supportive management of patients ( 5 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations